Medicina interna: - Chalem Benattar, Fernando; Campos Garrido, Jaime; Escandon Sorzano,Jorge Enrique; Esguerra Gutiérrez, Roberto (Editorial NORMA, 1986)
Enfermedades del riñon.- Enfermedades de la sangre.- Trastornos hormonales.